Biomechanical effects of screw loosening after lumbar PEEK rod and titanium rod fixation: a finite element analysis - Jiang, Guozheng; Wang, Shuyang; Xu, Luchun; Li, Zeyu; Feng, Ningning; Qiu, Ziye; Yang, Yongdong; Yu, Xing (Frontiers in Bioengineering and Biotechnology, 2025)
ObjectiveScrew loosening is a common complication following lumbar spine fixation surgery, yet the biomechanical outcomes after screw loosening remain rarely reported. This study aims to utilize finite element (FE) models to compare the biomechanical performance of PEEK rod dynamic fixation and titanium rod rigid fixation in the postoperative lumbar spine, exploring potential biomechanical mechanisms for re-stabilization of loosened screws.MethodsA FE model of the lumbar spine from L3 to the sacrum was developed using CT image segmentation. Four L4-S1 fixation models were constructed: PEEK rod dynamic fixation (PEEK model), titanium rod rigid fixation (titanium model), PEEK rod with pedicle screw loosening (PEEK-PSL model), and titanium rod with pedicle screw loosening (titanium -PSL model). A preload of 300 N was applied to the superior surface of L3. Stress distributions in the intervertebral discs, facet joints, pedicle screws, and rods were calculated to evaluate the biomechanical effects of different fixation methods.ResultsAcross four physiological loading conditions, the stress differences in intervertebral discs, facet joints, and nucleus pulposus between the PEEK model and titanium model were minimal. However, vertebral body stress was significantly higher in the PEEK model, whereas screw and rod stresses were greater in the titanium model. Screw loosening further increased stress in all models. The S1 screw in the PEEK-PSL model exhibited lower and more uniform stress, while stress was concentrated at the screw-rod junction in the titanium-PSL model.ConclusionThe PEEK rod fixation system demonstrated superior stress distribution, reducing stress concentration risks and improving stability while minimizing screw loosening rates. In contrast, the titanium rod system offers advantages in scenarios requiring high rigidity, potentially making it more suitable for patients with greater stability needs.